Organizational Culture, Work Environment, and Career Growth: Boosting Teacher Performance Through Motivation - Prasetyo Kurniawan; Nandang Hidayat (International Journal of Educational Administration, Management, and Leadership, 2025)
The study explores the impact of Organizational Culture, Work Environment, and Career Development on Teacher Performance through Teacher Work Motivation at Vocational High Schools (SMK) in Medan Sunggal District. Using a quantitative survey approach with a sample of 152 teachers, the study analyzed the data using PLS software version 3.0 (Partial Least Square). The findings reveal that both Organizational Culture and Teacher Work Motivation positively influence teacher performance, highlighting the importance of a strong organizational culture and motivated teachers in enhancing performance. In contrast, Work Environment and Career Development were not found to directly affect teacher performance, suggesting that while they influence daily conditions, they do not directly improve performance outcomes. The study also identified a negative relationship between Organizational Culture and Teacher Work Motivation, implying that a rigid or misaligned culture can hinder motivation. Furthermore, the Work Environment and Career Development were found to significantly impact teacher work motivation, underscoring the importance of a supportive and growth-oriented environment. Teacher Work Motivation was found to mediate the relationship between Organizational Culture and Work Environment on Teacher Performance, indicating that motivated teachers perform better when these factors are optimized. However, Teacher Work Motivation did not mediate the impact of Career Development on teacher performance, suggesting that career development alone may not be enough to enhance performance without proper motivation. The study emphasizes the need for a strong organizational culture and motivation in improving teacher performance, while also recognizing the limited direct role of career development and work environment.